Concrete for prefabricated part and preparation method thereof
By using a combination of high-content river sand and gravel, composite expanded particles and modified fibers in large volume concrete prefabricated components, the problem of prone to cracks in concrete during hydration and transportation is solved, and the effect of improving concrete strength and impact resistance is achieved.
Patent Information
- Application Number
- CN202411694056.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-28
AI Technical Summary
Large-volume concrete prefabricated components are prone to cracks during hydration, and surface bumps and cracks occur due to bumps during transportation, resulting in the strength of the prefabricated components not meeting expectations.
High content of river sand and gravel is used to combine composite expanded particles and modified fibers, and the porous heat dissipation effect of molecular sieve and the micro-expansion effect of composite expanded particles are used to reduce the internal temperature stress of concrete and increase the strength and impact resistance of concrete.
It effectively reduces the occurrence of cracks inside large-volume concrete and improves the impact resistance of the concrete surface, ensuring that prefabricated components are not prone to cracks and crushing during transportation, and ensuring that they still have high strength after transportation.
Smart Images

Figure BDA0005151697140000091 
Figure BDA0005151697140000101
Abstract
Description
Technical Field
[0001] The present application relates to the field of concrete, and more specifically, to concrete for prefabricated components and a preparation method thereof. Background Art
[0002] Precast concrete components are building components made in factories with concrete as the basic material. Common ones include precast concrete floor slabs, concrete box girders for bridges, precast concrete roof beams for industrial plants, culvert frames, precast concrete piles for foundation treatment, etc.
[0003] For prefabricated components used in box girders, culverts, foundations and other fields, large-volume concrete components are generally used. However, due to its large volume, large-volume concrete is prone to cracks during the hydration process due to the large temperature difference between the internal and external surfaces. In addition, prefabricated components need to be transported to the construction site, and are prone to bumps and breakages, cracks and other problems on their surfaces during transportation. Large-volume concrete components are easily affected by internal cracks during transportation and external cracks during transportation, which can easily make the prefabricated components fail to meet the expected requirements when they arrive at the construction site.
[0004] Therefore, how to prepare a concrete suitable for large-volume prefabricated components, the prepared large-volume prefabricated components are not prone to cracks inside, while having high surface strength and are not prone to surface bumps and cracks during transportation, thereby ensuring the strength of the prefabricated components. Summary of the invention
[0005] In order to prepare a concrete suitable for large-volume prefabricated components, the prepared large-volume prefabricated components are not prone to cracks inside, have high surface strength, are not prone to surface bumps and cracks during transportation, and ensure the strength of the prefabricated components, the application provides a concrete for prefabricated components and a preparation method thereof.
[0006] In a first aspect, the present application provides a concrete for prefabricated components, which adopts the following technical solution: A concrete for prefabricated components, the concrete comprising the following raw materials in parts by weight: 350-380 parts of cement, 820-860 parts of river sand, 850-960 parts of toughened epoxy resin modified crushed stone, 130-150 parts of water, 45-55 parts of mineral powder, 25-35 parts of fly ash, 8.3-9.0 parts of water reducing agent, 5-10 parts of molecular sieve loaded polyamide curing agent, 5-10 parts of composite expansion particles, and 5-10 parts of modified fiber.
[0007] By adopting the above technical scheme, the amount of crushed stone and river sand added is relatively high, and they can be evenly dispersed in the concrete. The filling and reinforcing effect of the composite expansion particles and modified fibers can be combined to further increase the strength of large-volume concrete; and the porous heat dissipation effect of the molecular sieve is combined with the micro-expansion effect of the composite expansion particles to reduce the internal temperature stress of the large-volume concrete, compensate for the shrinkage of the concrete, and reduce the generation of cracks in the concrete; at the same time, the better impact toughness of the surface of the crushed stone modified by the tough epoxy resin is used to further improve the impact resistance of the crushed stone on the concrete surface of the prefabricated components, and the cross-linking effect of the polyamide curing agent and the tough epoxy resin in the molecular sieve-loaded polyamide curing agent is combined to further improve the impact resistance of the large-volume concrete used for the prefabricated components. During transportation, the concrete is not prone to surface cracking and breaking due to impact and collision, thereby ensuring that the concrete for the prefabricated components still has a high strength after being transported to the construction site.
[0008] Preferably, the toughened epoxy resin modified gravel is prepared by the following method: The fatty acid-modified silicone epoxy resin and the polyethylene glycol solution are mixed and stirred evenly at a mass ratio of 1:2-4 to obtain a resin liquid, and the resin liquid is evenly sprayed on the surface of the crushed stone at a mass ratio of 40-80:1000, and the crushed stone is evenly dispersed to obtain a finished product.
[0009] By adopting the above technical scheme, the fatty acid-modified silicone epoxy resin is easy to be evenly attached to the surface of the crushed stone under the dilution effect of the polyethylene glycol solution, and the limit of the dosage ratio is used to ensure that adjacent crushed stones will not stick together, and the surface of the crushed stone is loaded with fatty acid-modified silicone epoxy resin and polyethylene glycol while ensuring the dispersion effect of the crushed stone; after the crushed stone contacts with cement, during the hydration process, the solvent in the polyethylene glycol solution continuously flows away, which can reduce the internal heat of the large-volume concrete and control the generation of cracks inside the large-volume concrete; at the same time, during the cross-linking process of the fatty acid-modified silicone epoxy resin and the polyamide curing agent, the polyethylene glycol can further promote the formation of the cross-linking network, which is easy to produce a folded epoxy resin network with good toughness, thereby improving the toughness of the crushed stone surface and making the crushed stone surface have a higher impact resistance effect. For the crushed stone that occupies the largest content in the concrete of the prefabricated component, its toughness and impact resistance are combined with rigid strength to further protect the prefabricated component from cracks during transportation, thereby ensuring the strength and use effect of the finished product.
[0010] Preferably, the molecular sieve-loaded polyamide curing agent is prepared by the following method: The molecular sieve is placed in a polyamide curing agent at a mass ratio of 1:8-12 and dispersed evenly, then the molecular sieve is filtered out, the surface is evenly sprayed with polycaprolactone liquid, and then silicon dioxide whiskers are evenly added, the weight ratio of the molecular sieve to the polycaprolactone liquid and the silicon dioxide whiskers is 1:0.3-0.6:0.2-0.4, and the surface of the polycaprolactone liquid is dried at room temperature and then dispersed to obtain a finished product.
[0011] By adopting the above technical scheme, the molecular sieve has a porous structure. The porous adsorption effect of the molecular sieve and the loading effect of a large specific surface area are utilized to facilitate the molecular sieve to load a polyamide curing agent liquid with low viscosity. Then, the bonding effect of the polycaprolactone liquid is utilized to adhere the silicon dioxide whiskers to the surface of the molecular sieve adsorbed with the polyamide curing agent. At room temperature, the polycaprolactone forms a film, while the polyamide curing agent is still in a liquid state.
[0012] During the cement hydration process, due to the high hydration temperature of large-volume concrete, which can generally reach 70°C, but the hydration temperature rise is a process. In the early stage of the hydration reaction, the temperature has not reached the melting point of polycaprolactone, but the cement hydration causes gradual expansion. The thorny structure of the silica whisker is used to pierce the film formed by the polycaprolactone liquid, so that the polyamide curing agent is gradually released. As the hydration reaction temperature increases, it reaches the melting point of polycaprolactone at about 60°C. The polycaprolactone gradually melts and promotes the further release of the polyamide curing agent. With the drainage effect of the silica whisker, the polyamide curing agent gradually contacts with the tough epoxy resin modified gravel. With the supporting skeleton effect of the silica whisker, after the hydration is completed, the tough epoxy resin cross-linking network is completed. It is not only tough, but also strong, so that the prefabricated components are not prone to bumps and cracks during transportation.
[0013] Preferably, the composite expanded particles are composed of calcium sulphoaluminate, polycarbonate and perlite in a mass ratio of 1:1-2:1-2.
[0014] By adopting the above technical scheme, as the hydration reaction proceeds, calcium sulfoaluminate gradually expands slightly to fill the shrinkage cracks inside the concrete, thereby further ensuring the strength of the concrete; combined with the lightweight effect of polycarbonate and perlite, it is convenient to fill the gaps dispersed inside the concrete, and combined with its higher strength and better toughness, the impact resistance and strength of the concrete are further increased, making it less likely for the concrete to crack due to collision during transportation.
[0015] Preferably, the average particle size of the calcium sulfoaluminate is 20-35 μm, the average particle size of the polycarbonate is 40-80 μm, and the average particle size of the loaded perlite is 80-150 μm.
[0016] By adopting the above technical solution, the particle size of the composite expansion particles is limited to present a gradient state, thereby ensuring the filling effect of the composite expansion particles, thereby making the concrete for prefabricated components have higher strength.
[0017] Preferably, the polycarbonate is prepared from polycarbonate particles and polyethylenediamine solution in a mass ratio of 1:0.1-0.25.
[0018] By adopting the above technical scheme, the surface of the polycarbonate particles is loaded with a polyethylenediamine solution, and the amino group in the polyethylenediamine is utilized to form a cross-linked network with fatty acid-modified silicone epoxy resin, polyethylene glycol solution, and polyamide curing agent, thereby further improving the impact toughness of the crushed stone surface and ensuring that the concrete for prefabricated components is not prone to cracks due to collision during transportation.
[0019] Preferably, the loaded perlite is made of porous expanded perlite particles and a silane coupling agent in a mass ratio of 1:0.2-0.5.
[0020] By adopting the above technical scheme, the adsorption effect of porous expanded perlite particles is utilized to facilitate the adsorption of silane coupling agents, further promoting the connection between silica whiskers and epoxy resin cross-linking networks, thereby further improving the strength of prefabricated components, and combining the air permeability of the porous structure of perlite and the air permeability effect of the molecular sieve to control the generation of cracks inside large-volume concrete, thereby ensuring that the concrete used for prefabricated components has a higher strength.
[0021] Preferably, the modified fiber is made of polycaprolactone diol liquid, polyacrylonitrile fiber and glass fiber in a mass ratio of 1:1-3:1-2.
[0022] By adopting the above technical scheme, the polycaprolactone diol liquid adheres to the surface of polyacrylonitrile fiber and glass fiber, and utilizes the water-insolubility and drainage effect of the fiber to facilitate the circulation of the polyamide curing agent and contact with the fatty acid-modified silicone epoxy resin, thereby promoting the formation of a tough folded epoxy resin network, improving the impact resistance of concrete for prefabricated components, and ensuring the strength of the concrete.
[0023] Preferably, the water reducer is a polycarboxylic acid high-efficiency water reducer.
[0024] By adopting the above technical solution, a better water reduction effect is achieved, ensuring the strength of the finished large-volume precast concrete components.
[0025] In a second aspect, the present application provides a method for preparing concrete for prefabricated components, which adopts the following technical solution: The method for preparing concrete for prefabricated components comprises the following steps: S1. Weigh cement and river sand, mix and stir evenly, then add mineral powder and fly ash, mix and stir evenly to obtain a primary mixture; S2, mixing the toughened epoxy resin modified crushed stone and the molecular sieve loaded polyamide curing agent evenly, then adding the composite expansion particles and mixing evenly to obtain a composite material; adding the composite material and the modified fiber to the primary mixture, and finally adding water and a water reducing agent and mixing evenly to obtain a mixture; S3. The mixture is poured and cured to obtain finished concrete.
[0026] By adopting the above technical scheme, tough epoxy resin modified crushed stone is mixed with molecular sieve loaded polyamide curing agent, which increases the contact area between the two, promotes the formation of a flexible folded epoxy resin network, and combines the filling and supporting effects of composite expanding particles and fibers to further improve the strength and impact resistance of concrete, making it less likely for concrete for prefabricated components to crack due to collision during transportation.
[0027] In summary, this application has the following beneficial effects: 1. The amount of crushed stone and river sand added is relatively high, and the filling and strengthening effect of composite expansion particles and modified fibers are combined to further increase the strength of large-volume concrete. The porous heat dissipation effect of molecular sieves is combined with the micro-expansion effect of composite expansion particles to reduce the internal temperature stress of large-volume concrete, compensate for concrete shrinkage, and control the generation of cracks inside concrete. At the same time, the cross-linking effect of polyamide curing agent and tough epoxy resin in molecular sieve-loaded polyamide curing agent further improves the impact resistance of large-volume concrete used for prefabricated components. During transportation, it is not easy for concrete to crack or break on the surface due to impact or collision, ensuring that the concrete for prefabricated components still has high strength after being transported to the construction site.
[0028] 2. The tough epoxy resin formed by the combination of fatty acid-modified silicone resin and polyamide curing agent has a certain waterproof effect and high strength and toughness. Combined with the waterproof effect of polycaprolactone, the waterproof effect of prefabricated components is further improved. At the same time, combined with the toughness of polycaprolactone diol and the toughness and impact resistance of polyacrylonitrile fiber and polycarbonate, the impact and collision resistance of concrete for prefabricated components are further improved, and collision cracks are not easy to occur during transportation.
[0029] 3. The combination of fatty acid-modified silicone resin, polyamide curing agent, polyethylene glycol, and polyethylenediamine on the surface of polycarbonate can further promote the formation of a foldable tough epoxy resin network through the cross-linking effect, which can further improve the impact and collision resistance of concrete for prefabricated components, thereby ensuring that prefabricated components are not prone to cracks due to collisions during transportation. DETAILED DESCRIPTION
[0030] The present application is further described in detail below in conjunction with embodiments.
[0031] Example of Preparation of Tough Epoxy Resin Modified Crushed Stone The following raw materials are all commonly available on the market.
[0032] Preparation Example 1: Tough epoxy resin modified crushed stone is prepared by the following method: Weigh 100 g of silicone epoxy resin, 89.5 g of dimer fatty acid and 1.0 g of tetrabutylammonium bromide, mix and stir evenly, react at 125° C., nitrogen protection, 200 r / min for 1 h, then heat to 135° C. and keep for 10 min, the epoxy equivalent is 5%, and fatty acid-modified silicone epoxy resin is obtained; 1kg of fatty acid modified silicone epoxy resin is mixed and stirred evenly with 3kg of polyethylene glycol solution, wherein the polyethylene glycol solution is a polyethylene glycol ethanol solution with a mass fraction of 10%, the polyethylene glycol is polyethylene glycol 4000, and the mass fraction of ethanol is 99%, to obtain a resin liquid; 60kg of the resin liquid is evenly sprayed on the surface of 1000kg of crushed stone, the particle size of the crushed stone is 5-25mm continuously graded, and the mud content is less than 1%; the crushed stones are dispersed until they are not adhered to each other and are evenly dispersed to obtain a finished product.
[0033] Preparation Example 2: This preparation example differs from Preparation Example 1 in that: 1 kg of fatty acid-modified silicone epoxy resin and 2 kg of polyethylene glycol solution were mixed and stirred evenly to obtain resin liquid; 40 kg of the resin liquid was sprayed evenly on the surface of 1000 kg of crushed stones; the crushed stones were dispersed until they were not adhered to each other and were evenly dispersed to obtain a finished product.
[0034] Preparation Example 3: This preparation example differs from Preparation Example 1 in that: 1 kg of fatty acid-modified silicone epoxy resin and 4 kg of polyethylene glycol solution were mixed and stirred evenly to obtain resin liquid; 80 kg of the resin liquid was sprayed evenly on the surface of 1000 kg of crushed stones; the crushed stones were dispersed until they were not adhered to each other and were evenly dispersed to obtain a finished product.
[0035] Preparation Example of Molecular Sieve Supported Polyamide Curing Agent The polyamide curing agent was purchased from polyamide curing agent 651 produced by Jinan Jibin Chemical Co., Ltd.; other raw materials were all commercially available.
[0036] Preparation Example 4: Molecular sieve-loaded polyamide curing agent is prepared by the following method: 1 kg of molecular sieve was placed in 10 kg of polyamide curing agent, the average particle size of the molecular sieve was 80 μm, and ultrasonic dispersion was carried out at 20 kHz for 15 minutes. After uniform dispersion, the molecular sieve was filtered out, 0.5 kg of polycaprolactone liquid was sprayed evenly on the surface, and then 0.3 kg of silica whisker was added, and the addition rate of the silica whisker was 60 g / min. During the addition process, the stirring rate of the molecular sieve was 120 r / min. The average length of the silica whisker was 40 μm, and the average diameter was 20 nm. The polycaprolactone liquid was obtained by heating polycaprolactone to 65°C and hot-melting it. The molecular weight of polycaprolactone was 20,000. After air-drying at room temperature until the surface of the polycaprolactone liquid was dry and formed into a film, the molecular sieves were dispersed until they did not stick to each other and agglomerated to obtain a finished product.
[0037] Preparation Example 5: This preparation example differs from Preparation Example 4 in that: 1 kg of molecular sieve was placed in 8 kg of polyamide curing agent, the average particle size of the molecular sieve was 80 μm, and ultrasonic dispersion was carried out at 20 kHz for 15 minutes. After uniform dispersion, the molecular sieve was filtered out, 0.3 kg of polycaprolactone liquid was sprayed evenly on the surface, and then 0.2 kg of silica whisker was added at a rate of 60 g / min. During the addition process, the molecular sieve was stirred at a rate of 120 r / min. After air-drying at room temperature until the surface of the polycaprolactone liquid was dry and formed into a film, the molecular sieves were dispersed until they did not stick to each other and agglomerate to obtain a finished product.
[0038] Preparation Example 6: This preparation example differs from Preparation Example 4 in that: 1 kg of molecular sieve was placed in 12 kg of polyamide curing agent, the average particle size of the molecular sieve was 80 μm, and ultrasonic dispersion was carried out at 20 kHz for 15 minutes. After uniform dispersion, the molecular sieve was filtered out, 0.6 kg of polycaprolactone liquid was sprayed evenly on the surface, and then 0.4 kg of silica whisker was added at a rate of 60 g / min. During the addition process, the molecular sieve was stirred at a rate of 120 r / min. After air-drying at room temperature until the surface of the polycaprolactone liquid was dry and formed into a film, the molecular sieves were dispersed until they did not stick to each other and agglomerate to obtain a finished product.
[0039] Preparation Example of Polycarbonate The following raw materials are all commercially available.
[0040] Preparation Example 7: Polycarbonate was prepared by the following method: 0.2 kg of polyethylenediamine solution was evenly sprayed on the surface of 1 kg of polycarbonate particles, and then dried and dispersed until the polycarbonate particles did not stick to each other and agglomerated to obtain a finished polycarbonate with an average particle size of 60 μm; the polyethylenediamine solution was a polyethylenediamine aqueous solution with a mass fraction of 2%.
[0041] Preparation Example 8: This preparation example differs from Preparation Example 7 in that: 0.1 kg of polyethylenediamine solution was evenly sprayed on the surface of 1 kg of polycarbonate particles, and the solution was dried and dispersed until the polycarbonate particles did not stick to each other and agglomerated, thereby obtaining a finished polycarbonate having an average particle size of 40 μm.
[0042] Preparation Example 9: This preparation example differs from Preparation Example 7 in that: 0.25 kg of polyethylenediamine solution was evenly sprayed on the surface of 1 kg of polycarbonate particles, and the solution was dried and dispersed until the polycarbonate particles did not stick to each other and agglomerated, thereby obtaining a finished polycarbonate with an average particle size of 80 μm.
[0043] Preparation Example of Loaded Perlite The following raw materials are all commercially available.
[0044] Preparation Example 10: The loaded perlite is prepared by the following method: 0.35 kg of silane coupling agent was added to 1 kg of porous expanded perlite particles, the average porosity of the porous expanded perlite particles was 65%, and the particles were continuously stirred at a speed of 200 r / min during the adding process. After uniform stirring for 20 minutes, loaded perlite was obtained, the average particle size of the loaded perlite was 100 μm, and the silane coupling agent was silane coupling agent KH-550.
[0045] Preparation Example 11: This preparation example differs from Preparation Example 10 in that: 0.2 kg of silane coupling agent was added to 1 kg of porous expanded perlite particles. During the addition process, the mixture was continuously stirred at a speed of 200 r / min. After uniform stirring for 20 minutes, loaded perlite was obtained. The average particle size of the loaded perlite was 80 μm.
[0046] Preparation Example 12: This preparation example differs from Preparation Example 10 in that: 0.5 kg of silane coupling agent was added to 1 kg of porous expanded perlite particles. During the addition process, the mixture was continuously stirred at a speed of 200 r / min. After uniform stirring for 20 minutes, loaded perlite was obtained. The average particle size of the loaded perlite was 150 μm.
[0047] Preparation example of modified fiber The following raw materials are all commercially available.
[0048] Preparation Example 13: The modified fiber was prepared by the following method: The polycaprolactone diol is heated to 65°C to completely melt to obtain a polycaprolactone diol liquid, the average molecular weight of the polycaprolactone diol is 3000, 1 kg of the polycaprolactone diol liquid is evenly sprayed on the surface of 2 kg of polyacrylonitrile fiber and 1.5 kg of glass fiber, and then dried and dispersed until the polyacrylonitrile fiber and the glass fiber are not adhered to each other to obtain modified fibers; the average length of the polyacrylonitrile fiber is 3 mm, and the average length of the glass fiber is 2 mm.
[0049] Preparation Example 14: This preparation example differs from Preparation Example 13 in that: 1 kg of polycaprolactone diol liquid was evenly sprayed on the surface of 1 kg of polyacrylonitrile fiber and 1 kg of glass fiber, and the liquid was dried and dispersed until the polyacrylonitrile fiber and the glass fiber were not adhered to each other, thereby obtaining modified fibers.
[0050] Preparation Example 15: This preparation example differs from Preparation Example 13 in that: 1 kg of polycaprolactone diol liquid was evenly sprayed on the surface of 3 kg of polyacrylonitrile fiber and 2 kg of glass fiber, and the liquid was dried and dispersed until the polyacrylonitrile fiber and the glass fiber were not adhered to each other, thereby obtaining modified fibers. Example
[0051] Among the following raw materials, the polycarboxylate high-efficiency water-reducing agent was purchased from Shanghai Hengchuang Chemical Co., Ltd.; other raw materials are all commercially available.
[0052] Example 1: Concrete for prefabricated components: 360kg cement, 840kg river sand, 900kg toughened epoxy resin modified crushed stone, 140kg water, 50kg mineral powder, 30kg fly ash, 8.8kg water reducer, 8kg molecular sieve loaded polyamide curing agent, 8kg composite expansion particles, 8kg modified fiber; cement is silicate cement with P.O42.5; river sand is medium sand in zone II, with an apparent density of 2660kg / m 3 , fineness modulus is 2.5, mud content is less than 1.0%; tough epoxy resin modified crushed stone is the finished product prepared in Preparation Example 1; the mineral powder is S95 grade slag powder, density is 2.8g / cm 3 , with a specific surface area of 420m 2 / kg, activity index (7d) is 82%, activity index (28d) is 94%, fluidity ratio is 96%, water content is 0.2%; fly ash is F class II fly ash, fly ash fineness (45μm square hole sieve residue) is 8%, loss on ignition is <4.5%, water requirement ratio is <96%, water content is <0.2%; water reducer is polycarboxylic acid high efficiency water reducer; molecular sieve loaded polyamide curing agent is the finished product prepared in Preparation Example 4; composite expanded particles are composed of calcium sulfoaluminate, polycarbonate prepared in Preparation Example 7 and loaded perlite prepared in Preparation Example 10 in a mass ratio of 1:1.5:1.5, and the average particle size of calcium sulfoaluminate is 30μm; modified fiber is the finished product prepared in Preparation Example 13; The preparation method is as follows: S1. Weigh cement and river sand, mix and stir evenly, then add mineral powder and fly ash, mix and stir evenly to obtain a primary mixture; S2, mixing the toughened epoxy resin modified crushed stone and the molecular sieve loaded polyamide curing agent evenly, and then adding the reinforcing particles and mixing evenly to obtain a composite material; adding the composite material and the modified fiber to the primary mixture, and finally adding water and a water reducing agent and mixing evenly to obtain a mixture; S3. The mixture is poured and cured to obtain finished concrete.
[0053] Embodiment 2: This embodiment differs from Embodiment 1 in that: 350kg cement, 820kg river sand, 850kg tough epoxy resin modified gravel, 130kg water, 45kg mineral powder, 25kg fly ash, 8.3kg water reducer, 5kg molecular sieve loaded polyamide curing agent, 5kg composite expansive particles, 5kg modified fiber; the tough epoxy resin modified gravel is the finished product prepared in Preparation Example 2; the molecular sieve loaded polyamide curing agent is the finished product prepared in Preparation Example 5; the composite expansive particles are composed of calcium sulfoaluminate, polycarbonate prepared in Preparation Example 8 and perlite loaded in Preparation Example 11 in a mass ratio of 1:1:1, and the average particle size of the calcium sulfoaluminate is 20μm; the modified fiber is the finished product prepared in Preparation Example 14.
[0054] Embodiment 3: This embodiment differs from Embodiment 1 in that: 380kg cement, 860kg river sand, 960kg tough epoxy resin modified gravel, 150kg water, 55kg mineral powder, 35kg fly ash, 9.0kg water reducer, 10kg molecular sieve loaded polyamide curing agent, 10kg composite expansive particles, 10kg modified fiber; the tough epoxy resin modified gravel is selected from the finished product prepared in Preparation Example 3; the molecular sieve loaded polyamide curing agent is selected from the finished product prepared in Preparation Example 6; the composite expansive particles are composed of calcium sulfoaluminate, polycarbonate prepared in Preparation Example 9 and perlite loaded in Preparation Example 12 in a mass ratio of 1:2:2, and the average particle size of the calcium sulfoaluminate is 35μm; the modified fiber is selected from the finished product prepared in Preparation Example 15.
[0055] Embodiment 4: This embodiment differs from Embodiment 1 in that: During the preparation of toughened epoxy resin modified crushed stone in the raw materials, no polyethylene glycol solution was added.
[0056] Embodiment 5: This embodiment differs from Embodiment 1 in that: During the preparation of the molecular sieve-loaded polyamide curing agent in the raw materials, no polycaprolactone liquid and silica whiskers were added.
[0057] Embodiment 6: This embodiment differs from Embodiment 1 in that: No calcium sulphoaluminate is added to the composite expanded particles in the raw materials.
[0058] Embodiment 7: This embodiment differs from Embodiment 1 in that: The composite expanded particles in the raw materials are replaced by polycarbonate particles of equal mass, and the loaded perlite is replaced by perlite particles of equal mass.
[0059] Embodiment 8: This embodiment differs from Embodiment 1 in that: No polycaprolactone diol liquid was added to the raw materials during the preparation of the modified fiber.
[0060] Comparative Example Comparative Example 1: The difference between this comparative example and Example 1 is that: In the raw materials, the toughened epoxy resin modified crushed stone is replaced by crushed stone of equal mass, and the molecular sieve loaded polyamide curing agent is replaced by molecular sieve of equal mass.
[0061] Comparative Example 2: The difference between this comparative example and Example 1 is that: The composite expanded particles are replaced by perlite particles of equal mass in the raw materials, and the average particle size of the perlite particles is 100 μm.
[0062] Comparative Example 3: The difference between this comparative example and Example 1 is that: The modified fiber is replaced by polypropylene fiber of equal quality in the raw material.
[0063] Performance testing 1. Strength detection Concrete was prepared by the methods of Examples 1-8 and Comparative Examples 1-3, respectively. A test specimen with a volume of 1 cubic meter was used, and the compressive strength after curing for 7 days and 28 days was tested with reference to GB / T50081. After 28 days, the specimen was hammered evenly on the surface of the specimen for 60 times with a hammering amount of 1 kg / time, and then the compressive strength was continued to be tested and the data was recorded.
[0064] 2. Crack detection Concrete was prepared by the methods of Examples 1-8 and Comparative Examples 1-3, respectively. A test specimen with a volume of 1 cubic meter was used, and the crack area per unit area was recorded 48 hours after pouring. After curing for 28 days, the specimen was hammered evenly on the surface of the specimen for 60 times with a hammering amount of 1 kg / time, and then the crack area per unit area was continued to be recorded, and the data was recorded.
[0065] 3. Slump test The methods of Example 1 were used to prepare concrete, and the slump of the concrete was tested and the data was recorded.
[0066] Table 1 Performance test table It can be seen from Examples 1-3 and Table 1 that the concrete for prefabricated components prepared in the present application has high strength, and after impact, the strength loss is less, and at the same time, the concrete has fewer cracks, and the cracks after impact are still fewer, indicating that the large-volume concrete used for prefabricated components has high strength and is not prone to surface cracking and breakage of the concrete due to impact or collision, thereby ensuring that the concrete for prefabricated components still has high strength after being transported to the construction site.
[0067] Combining Example 1 and Examples 4-8 and Table 1, it can be seen that in the preparation process of the toughened epoxy resin modified crushed stone in the raw material of Example 4, no polyethylene glycol solution was added. Compared with Example 1, the compressive strength of the concrete prepared in Example 4 was lower than that in Example 1, and the crack area was larger than that in Example 1; this indicates that the polyethylene glycol solution is cross-linked with the cross-linked epoxy resin and the polyamide curing agent, further increasing the cross-linked network area inside the concrete, thereby improving the strength and crack resistance of the concrete.
[0068] During the preparation of the molecular sieve-loaded polyamide curing agent in the raw materials of Example 5, polycaprolactone liquid and silica whiskers were not added. Compared with Example 1, the compressive strength of the concrete prepared in Example 5 was lower than that in Example 1, and the crack area was larger than that in Example 1. This indicates that the cooperation between polycaprolactone liquid and silica whiskers can gradually promote the release of the polyamide curing agent during the hydration process, thereby facilitating the cross-linking of the polyamide curing agent with the epoxy resin to obtain a cross-linked network with good toughness, which can resist impact and ensure the strength and crack resistance of the concrete.
[0069] No calcium sulfoaluminate was added to the composite expansive particles in the raw materials of Example 6. Compared with Example 1, the compressive strength of the concrete prepared in Example 6 was lower than that in Example 1, and the crack area was larger than that in Example 1, indicating that calcium sulfoaluminate can slightly expand and fill the internal gaps of large-volume concrete, thereby ensuring the strength and durability of concrete for prefabricated components.
[0070] In Example 7, the composite expanded particles in the raw materials are replaced with polycarbonate particles of equal mass, and the loaded perlite is replaced with perlite particles of equal mass. Compared with Example 1, the compressive strength of the concrete prepared in Example 7 is lower than that in Example 1, and the crack area is larger than that in Example 1; this indicates that the polyethylenediamine on the surface of polycarbonate can be cross-linked with the tough epoxy resin modified gravel and the molecular sieve loaded polyamide curing agent, thereby improving the density of the internal structure of the concrete, improving the strength of the concrete and the impact resistance of the gravel surface, and ensuring that the large-volume concrete for prefabricated components has higher strength and longer service life.
[0071] In the process of preparing the modified fiber in the raw materials of Example 8, no polycaprolactone diol liquid was added. Compared with Example 1, the compressive strength of the concrete prepared in Example 8 was lower than that in Example 1, and the crack area was larger than that in Example 1. This indicates that the polycaprolactone diol liquid adheres to the surface of the polyacrylonitrile fiber and the glass fiber, and utilizes the water-insolubility and drainage effects of the fiber to facilitate the circulation of the polyamide curing agent and the contact with the fatty acid-modified silicone epoxy resin, thereby promoting the formation of a tough folded epoxy resin network, improving the impact resistance of concrete for prefabricated components, and ensuring the strength of the concrete.
[0072] Combining Example 1 and Comparative Examples 1-3 and Table 1, it can be seen that in the raw materials of Comparative Example 1, the tough epoxy resin modified crushed stone is replaced by the same mass of crushed stone, and the molecular sieve loaded polyamide curing agent is replaced by the same mass of molecular sieve. Compared with Example 1, the compressive strength of the concrete prepared in Comparative Example 1 is lower than that in Example 1, and the crack area is larger than that in Example 1; this indicates that during the hydration process, during the cross-linking process of the fatty acid-modified silicone epoxy resin and the polyamide curing agent, the polyethylene glycol can further promote the formation of the cross-linked network, which is convenient for producing the tough epoxy resin in a folded state, thereby improving the toughness of the crushed stone surface, so that the crushed stone surface has a higher impact resistance effect. For the crushed stone that occupies the largest content in the concrete of the prefabricated component, its toughness and impact resistance are combined with the rigid strength to further protect the prefabricated component from cracks during transportation, thereby ensuring the strength and use effect of the finished product.
[0073] In Comparative Example 2, the composite expanded particles are replaced with perlite particles of equal mass in the raw materials. Compared with Example 1, the compressive strength of the concrete prepared in Comparative Example 2 is lower than that in Example 1, and the crack area is larger than that in Example 1; this indicates that calcium sulfoaluminate gradually expands slightly to fill the shrinkage cracks inside the concrete, thereby further ensuring the strength of the concrete; combined with the lightweight effect of polycarbonate and perlite, it is convenient to fill the gaps dispersed in the concrete, and combined with its higher strength and better toughness, the impact resistance and strength of the concrete are further increased, making it less likely for the concrete to crack due to collision during transportation.
[0074] In Comparative Example 3, the modified fiber is replaced by polypropylene fiber of equal mass in the raw material. Compared with Example 1, the compressive strength of the concrete prepared in Comparative Example 3 is lower than that in Example 1, and the crack area is larger than that in Example 1; this indicates that the polyacrylonitrile fiber has good toughness and impact resistance, and the cross-linking effect of the polycaprolactone diol liquid further improves the strength and impact resistance of the concrete for prefabricated components, ensuring that the prefabricated components are not prone to cracks due to transportation impact, thereby affecting their service life.
[0075] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A concrete for prefabricated components, characterized in that: The concrete comprises the following raw materials in parts by weight: 350-380 parts of cement, 820-860 parts of river sand, 850-960 parts of toughened epoxy resin modified crushed stone, 130-150 parts of water, 45-55 parts of mineral powder, 25-35 parts of fly ash, 8.3-9.0 parts of water reducer, 5-10 parts of molecular sieve loaded polyamide curing agent, 5-10 parts of composite expansion particles, and 5-10 parts of modified fiber.
2. The concrete for prefabricated components according to claim 1, characterized in that: The tough epoxy resin modified crushed stone is prepared by the following method: The fatty acid-modified silicone epoxy resin and the polyethylene glycol solution are mixed and stirred evenly at a mass ratio of 1:2-4 to obtain a resin liquid, and the resin liquid is evenly sprayed on the surface of the crushed stone at a mass ratio of 40-80:1000, and the crushed stone is evenly dispersed to obtain a finished product.
3. The concrete for precast components according to claim 1, characterized in that: The molecular sieve-loaded polyamide curing agent is prepared by the following method: The molecular sieve is placed in a polyamide curing agent at a mass ratio of 1:8-12 and dispersed evenly, then the molecular sieve is filtered out, the surface is evenly sprayed with polycaprolactone liquid, and then silicon dioxide whiskers are evenly added, the weight ratio of the molecular sieve to the polycaprolactone liquid and the silicon dioxide whiskers is 1:0.3-0.6:0.2-0.4, and the surface of the polycaprolactone liquid is dried at room temperature and then dispersed to obtain a finished product.
4. The concrete for precast components according to claim 1, characterized in that: The composite expanded particles are composed of calcium sulphoaluminate, polycarbonate and perlite in a mass ratio of 1:1-2:1-2.
5. The concrete for precast components according to claim 4, characterized in that: The average particle size of the calcium sulfoaluminate is 20-35 μm, the average particle size of the polycarbonate is 40-80 μm, and the average particle size of the loaded perlite is 80-150 μm.
6. The concrete for precast components according to claim 4, characterized in that: The polycarbonate is prepared from polycarbonate particles and polyethylene diamine solution in a mass ratio of 1:0.1-0.
25.
7. The concrete for precast components according to claim 4, characterized in that: The loaded perlite is prepared from porous expanded perlite particles and a silane coupling agent in a mass ratio of 1:0.2-0.
5.
8. The concrete for precast components according to claim 1, characterized in that: The modified fiber is prepared from polycaprolactone diol liquid, polyacrylonitrile fiber and glass fiber in a mass ratio of 1:1-3:1-2.
9. The concrete for precast components according to claim 1, characterized in that: The water reducer is a polycarboxylic acid high efficiency water reducer.
10. The method for preparing concrete for prefabricated components according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Weigh cement and river sand, mix and stir evenly, then add mineral powder and fly ash, mix and stir evenly to obtain a primary mixture; S2, mixing the toughened epoxy resin modified crushed stone and the molecular sieve loaded polyamide curing agent evenly, then adding the composite expansion particles and mixing evenly to obtain a composite material; adding the composite material and the modified fiber to the primary mixture, and finally adding water and a water reducing agent and mixing evenly to obtain a mixture; S3. The mixture is poured and cured to obtain finished concrete.
Citation Information
Cited By
Aerated concrete block and lightweight heat-preservation sound-insulation composite block
CN121609546A
Aerated concrete floor support plate as well as preparation method and application thereof
CN122145093A
Slurry-extracting and viscosity-reducing type polycarboxylic acid water reducing agent suitable for low-cement-consumption concrete and preparation method of polycarboxylic acid water reducing agent
CN122145738A